A Facile Chemical Synthesis of Cu2O Nanocubes Covered with Co3O4 Nanohexagons for the Sensitive Detection of Glucose. Issue 7 (16th February 2016) - Velmurgan, Sakthi; Devasenathipathy, Rajkumar; Chen, Shen‐Ming; Wang, Sea‐Fue
Abstract: Copper (I) oxide nanocubes (Cu2 O NCs) covered with cobalt oxide nanohexagons (Co3 O4 NHs) were prepared through simple chemical method. Here, ascorbic acid is used as reducing and capping agent for the synthesis of nanocubes and nanohexagons. Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Energy‐dispersive X‐ray spectroscopy (EDX) and X‐ray diffraction spectroscopy (XRD) were employed to confirm the prepared nanocomposite. Cu2 O NCs−Co3 O4 NHs nanocomposite is drop cast on the glassy carbon electrode (GCE) for the fabrication of glucose sensor. The fabricated Cu2 O NCs−Co3 O4 NHs/GCE exhibited a better electrocatalytic activity towards the determination of glucose than that of individually fabricated Cu2 O NCs and Co3 O4 NHs modified GCE. Our finding exhibited a wide linear range from 1 μM to 5330 μM with LOD of 0.63 towards glucose. In addition, the sensor attained appreciable stability, repeatability and reproducibility. Practicality of the sensor was demonstrated in human serum samples. The main advantages of the fabricated sensor are simple, biocompatible, cost effective, fast response and highly stable electrode surface. Abstract :